EFFECTS OF ECONOMIC AND NON-ECONOMIC FACTORS ON DOMESTIC TOURISM DEMAND – A GENERAL-TO-SPECIFIC APPROACH - VO VAN CAN (Centre For Tourism Planning and Development, 2013)
The purpose of this paper is to investigate the effects of both economic and noneconomic factors on the domestic tourist flow to Khanh Hoa province in the long run and the short run by using the general-to-specific approach. The findings reveal that weather variables have a significant effect on the tourism demand in the short run and long run. Furthermore, a positive effect from the lagged dependent variable suggests that word-of-mouth recommendation to potential tourists provides good signs in term of the Khanh Hoa tourism industry. Also, the demand for Vietnamese tourists seems to be highly sensitive to tourism costs. Therefore, a small increase in consumer prices or transportation prices will result in a strong decline in the domestic tourism demand. Knowledge of effects of these variables on the domestic tourism demand is valuable to tourism operators in Khanh Hoa province.